Сутність та значення феномену корупції - Гладкий, В. В. (Південний регіональний центр НАПрН України, 2019)
Анотація. Феномен корупції, як відомо, характерний практично для всіх сфер життєдіяльності людини. При цьому, тотальне панування корупції у державі досягається за рахунок стратегічного поширення цього явища в інститутах, покликаних запобігати та протидіяти корупції, тобто тими інститутами влади, яким держава і суспільство виказує надзвичайно високу довіру, надаючи відповідні публічні владні функції. У той же час, визнаючи корупцію в якості одного з найбільш небезпечних феноменів, обумовлених людиною, сучасне українське суспільство є надзвичайно толерантним до хабарництва – базисної форми корупції, досить терпимо ставиться до інших форм проявів корупції. Критично аналізуючи етимологічне тло корупції, її соціально-правову природу, автор стверджує, що окреслений парадокс приховується у конфлікті натуральної та соціальної природи корупціонерів, котрі визначають сутність і значення феномену корупції. //// Аннотация. Феномен коррупции, как известно, характерен практически для всех сфер жизнедеятельности человека. При этом, тотальное господство коррупции в государстве достигается за счёт стратегического распространения данного явления в институтах, призванных предотвращать и противодействовать коррупции, т. е. теми институтами власти, которым государство и общество оказывает чрезвычайно высокое доверие, предоставляя соответствующие публичные властные функции. В то же время, признавая коррупцию в качестве одного из наиболее опасных явлений, обусловленных человеком, современное украинское общество представляется крайне толерантным к взяточничеству – базовой форме коррупции, а также достаточно терпимо относится к другим формам проявления коррупции. Критически анализируя этимологический фон коррупции, её социально-правовую природу, автор утверждает, что очерченный парадокс скрывается в конфликте натуральной и социальной природы коррупционеров, которые определяют сущность и значение феномена коррупции. //// Summary. The phenomenon of corruption, as we know, characterizes almost all the spheres of human activities. In this, the total domination of corruption within the state is being achieved through the strategic expediency of this phenomenon at institutes aimed at avoiding and counteracting the corruption, that is, by those authority institutes, which are being provided with an extremely high confidence by the state and society while granting with the appropriate public functions. At the same time, while recognizing corruption as one of the most dangerous phenomena caused by the human, the modern Ukrainian society is very tolerant of bribery – the basial form of corruption. The author argues that the pointed paradox is hidden within the conflict of the natural and social nature of corruptionists, who determine the essence and value of the phenomenon of corruption. While investigating critically the etymological essence of the corruption phenomenon, as well as the social and legal one, the author concludes that the fully-fledged determination of the essence and role of the corruption phenomenon is possible only in case of avoiding an unjustifiably naive, infantile understanding of the natural and social nature of a human, his opportunities in social life. That is why, after establishing the fact that the person commits corruption activities because, first of all, he is a human being with those psychophysiological features that facilitate acting in terms of corruption logics and, relatively, the corruption behavior model, it will be possible in the future to construct the state anti-corruption policy , based not on ephemeral approaches to the determination of corrupt behavior from outside, but from inside. However, this does not mean that external factors influencing human consciousness in the context of the issue under consideration should be categorically ignored, because these factors, certainly, play an important supporting role - they allow to “uncover” the corrupt nature of a person.
Сущность и значение феномена коррупции
Essence and value of the phenomenon of corruption
Keywords: cause of corruption; corruption; determination of corruption; essence of corruptor; human nature; phenomenon of corruption; psychology of corruption; rule of corruption; social pathology; господство коррупции; детерминация коррупции; коррупция; психология коррупции; социальная патология; сущность коррупционера; феномен коррупции; детермінація корупції; корупція; панування корупції; природа людини; психологія корупції; соціальна патологія; сутність корупціонера; феномен корупції